Upaya Pendampingan untuk Mengurangi Pengaruh Minuman Keras di Kalangan Remaja Desa Janapria - Wati, Nila Kusuma (Journal of Community Development and Empowerment, 2025)
Alcoholic beverages are one of the problems that often affect adolescent behavior and health, especially in rural areas such as Janapria Village. This study aims to identify the main causes of alcohol consumption among adolescents and to design effective mentoring efforts to reduce its impact. The research method used is a qualitative approach involving in-depth interviews, participatory observation, and focus group discussions (FGDs) with adolescents, parents, and local community leaders. The results of the study indicate that the main factors driving alcohol consumption among adolescents include social environmental influences, a lack of awareness about the negative impacts, and a shortage of positive activities for youth. The mentoring program implemented includes education about the dangers of alcohol, the development of life skills, and strengthening the role of families and communities in supporting a healthy lifestyle. Evaluation results show a decrease in alcohol consumption among adolescents after the program was implemented. This study concludes that community-based mentoring is an effective approach to addressing the issue of alcohol consumption among rural adolescents.